Online site visits using virtual collaborative spaces: A plan-reading activity on a digital building site. (August 2022) - Sun, Yuan; Albeaino, Gilles; Gheisari, Masoud; Eiris, Ricardo
Highlights: Traditional site visits present major logistical and accessibility challenges for educators. An online device-agnostic site visit using virtual collaborative spaces was developed. A between-subjects study against a Zoom®-based business-as-usual condition was conducted. The online site visit was rated positively for sense of presence and social presence. The online site visit can deliver collaborative contextualized learning for distance education. Abstract: Site visits or field trips have been a tool utilized by construction educators to engage students in active learning, assist traditional lessons, and attain stronger and deeper student learning experiences. Nevertheless, site visits present major logistical and accessibility challenges for educational institutions and instructors, reducing the number of students that have access to the benefits of such a technique. The limitations for site visits have further broadened recently, as the reality of the COVID-19 public health concerns has forced educators to move to online course delivery quickly and the majority of site visits have been canceled. The research goal of this paper is to present construction students with opportunities to enable online location-independent site visits where contextualized learning is dangerous, unsafe, or impossible to achieve. In this project, a virtual online learning environment was created to offer the affordances that provide an in-depth learning experience through collaborative communication for a plan-reading activity in a virtual space that resembles a real-world site visit to a building facility. This virtual online learning environment helped students to experience the physical and social aspects of the site visit while getting a collaborative opportunity to practice their plan-reading skills. A comparative study with a business-as-usual condition (online delivery through Zoom®) was conducted and the students' plan-reading performance and their feedback on the sense of presence, social presence, fatigue, and system usability was reported. The outcome of the study shows that such virtual collaborative site visits present unique opportunities to enable online delivery of spatiotemporal contexts of sites and offer an effective remote alternative when these learning opportunities are not available.